THE EFFECT OF AUDIT QUALITY ATTRIBUTES ON CLIENT SATISFACTION - Marthlin Novten van Harling; Supriyati Supriyati; Djuwari Djuwari (STIE Perbanas Surabaya, 2013)
This study aims to determine whether the quality attributes affect the quality of the audit clientsatisfaction. The primary data were taken through questionnaires using non probabilitysampling with convenience sample technique. The sample being processed consists of 37 respondentsthat financial managers of companies already involved in services, trades and industries.The statistical analysis is OLS (Ordinary Least Square) using SPSS version 17.0.The results of this study concluded that audit quality attributes are formed by the attributes ofexperience in audit, understanding industry customer to respond to the needs of the clientcomplying with common rules, the attitude of care, strong commitment to quality, audit firm,leadership participation doing work field properly, the participation of the audit committee,high ethical and not easily to believe simultaneously and partially are not influential significantlytoward the customer satisfaction. In this case, such finding is in terms of significancelevel each of audit quality has significance level above 0.05 or 5 percent.